‘Triage, transition, and transformation’: Advocacy discourse in urban school reform - Sarah Winchell Lenhoff; Jennifer M. Lewis; Ben Pogodzinski; Robert Dorigo Jones (Education Policy Analysis Archives, 2019)
Advocacy coalitions have the potential to be a vehicle for community-based education reform in urban school systems, where state legislatures have increasingly adopted top-down policies such as state takeover and accountability systems. Yet, coalitions are influenced by and create their own informal and formal power structures that can include or exclude certain stakeholders and perspectives. In this study, the Advocacy Coalition Framework was used alongside critical discourse analysis of interviews, documents, and more than 50 news articles to explore how power and ideology shaped policy in the Coalition for the Future of Detroit Schoolchildren. We find that personal stories, political loyalties, and prior reform experiences shaped the narratives of Coalition members. While discourse from and about the Coalition was narrower in scope and representation during a tough legislative battle, the group’s policy victories and organizational infrastructure created potential for substantive community-led reform in the years following. This suggests that community-based education reform may require advocates to strategically sequence the promotion of diverse stakeholder interests in order to achieve broad coalition goals.